Design of the DYNAMO study: a multi-center randomized controlled trial to investigate the effect of pre-thickened oral nutritional supplements in nursing home residents with dysphagia and malnutrition (risk) - Viviënne A. L. Huppertz; Nick van Wijk; Laura W. J. Baijens; Lisette C. P. G. M. de Groot; Ruud J. G. Halfens; Jos M. G. A. Schols; Ardy van Helvoort (BMC Geriatrics, 2020)
Abstract Background Oropharyngeal Dysphagia (OD) and malnutrition are frequently reported conditions in nursing home residents, and are often interrelated. Best care for dysphagic residents with, or at risk of, malnutrition should target adequate nutritional intake and the safety and efficacy of swallowing. The effect of oral nutritional supplements (ONS) suitable for nursing home residents with concurrent OD and malnutrition (risk) on nutritional status has not been investigated before. The current study aims to investigate the effect of daily use of a range of pre-thickened ONS on the body weight of nursing home residents with OD and malnutrition (risk) compared to standard OD and nutritional care. Methods / design The DYNAMO study is a randomized, controlled, multi-center, open label trial with two parallel groups. Study participants will be recruited in nursing homes of several care organizations in the south of the Netherlands. Study duration is 12 weeks. Residents in the control group will receive standard OD and nutritional care, and residents in the test group will receive standard OD and nutritional care with extra daily supplementation of pre-thickened ONS. The main outcome parameter is the difference in body weight change between the control and test groups. An a priori estimation of the required sample size per group (control / test) totals 78. Other outcome parameters are differences in: nutritional intake, health-related quality of life, OD-specific quality of life, activities of daily living, vital signs, and blood nutrient and metabolite levels. Discussion Regular ONS could address the nutritional needs of nursing home residents with malnutrition (risk), but might be too thin and unsafe for residents with OD. Pre-thickened ONS is suitable for residents with OD. It offers the advantage of being a ready-to-use amylase-resistant product available in several consistencies which are able to increase swallowing efficacy and safety. The DYNAMO study is the first to investigate the effects of pre-thickened ONS on nutritional status in nursing home residents with concurrent OD and malnutrition (risk). Trial registration Netherlands Trial Register (NTR): NTR NL7898. Registered 24 July 2019, https://www.trialregister.nl/trial/7898